Experimental investigation of a hybrid configuration of solar thermal collectors and desiccant indirect evaporative cooling system - Ditta, Allah; Tabish, Asif Nadeem; Mujtaba, M. A.; Amjad, Muhammad; Yusuf, Abdulfatah Abdu; Chaudhary, Ghulam Qadar; Razzaq, Luqman; Abdelrahman, Anas; Kalam, M. A (Frontiers in Energy Research, 2022)
This paper presents the integrated performance of a solar assisted desiccant dehumidifier along with Maisotsenko cycle (M-cycle) counter flow heat and mass exchanger. This system handles latent load and sensible load separately. The hybrid configuration of solar thermal collectors was analyzed for efficiency of solar collectors and solar fraction. High consumption of fossil fuels, which are already present in a limited amount, is also associated with the environmental problems and climate change issues which in return increases the chances of global warming as well. These issues are demanding to shift towards the renewable energy resources. Increase in world energy use results in a number of environmental problems i.e. climate change in addition with global warming and ozone depletion. In building services HVAC systems are the major concerns. To overcome the requirement mainly conventional air conditioning and vapor compression systems are used for air conditioning which in term have some environmental problems. Solar thermal applications in combination with other renewable energy dependent cooling practices have created a huge interest towards sustainable solutions keeping in view several techno-economical, environmental and climatic advantages. The experimental investigation reveals that the maximum outlet temperature and efficiency of solar thermal collectors was 87 oC and 56% respectively. The Maximum cooling capacity of system evaluated is 4.6 kW.